Determinant Analysis Of Open Defecation with Stunting Incidence in Aceh Singkil District - Adelina Irmayani Lubis; Khairunnas; Enda Silvia Putri; Teuku Muliadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Stunting is a nutritional problem in Indonesia that is a cross-sectoral problem due to its complex and multifactor causal factors. The government has a role of involvement and capacity in stunting reduction interventions. One of the determinants of stunting in Aceh Singkil District is open defecation which is an indicator of WASH (Water, Sanitation, Hygiene) that contributes to the incidence of inflammatory diseases. This study aims to analyze the determinant of open defecation with stunting incidence in Aceh Singkil District. This study used a qualitative design with Focus Group Discussion data collection techniques for the regional working unit in Aceh Singkil District. The results showed that open defecation is still one of the causes of stunting in Aceh Singkil District where open defecation behavior still exists, such as digging landfills, flying toilets, and public bathing, washing, and toilet facilities in rivers. The problems related to this are the low level of proper drinking water facilities, the behavior of open defecation, and the lack of clean water sources. The conclusion is that there is a need for support from policymakers in improving specific interventions carried out by cross-sectors, especially the rules on Gampoeng for residents who are still doing defecation.